Global research trends and hotspots of oxidative stress in diabetic retinopathy (2000-2024) - Du, Kejie; Liu, Yichong; Zhao, Xintong; Wang, Haowen; Wan, Xiaomei; Sun, Xiaoyan; Luo, Wenjuan (Frontiers in Endocrinology, 2024)
The incidence of diabetic retinopathy, a major complication of diabetes, has been increasing annually, posing a serious threat to patients' vision and quality of life. As a result, numerous studies have been conducted over the years to investigate the pathogenic mechanisms of DR. Among these mechanisms, oxidative stress has been identified as a major contributor to the pathogenesis of DR, and many diagnostic and therapeutic strategies have been developed to target oxidative stress. Oxidative stress has become a popular research topic due to its potential implications. While some reviews have covered the molecular mechanisms and pathophysiology of oxidative stress in DR, there is a need for further analysis and summary of current research trends and hotspots in the field. To fill this gap, we conducted a bibliometric analysis of the relevant literature. Our aim was to understand the contribution of the country of origin of the publication, the institution, the authors, and the collaborative relationship between them. We also analyzed the highly cited literature and assessed the current research trends and emerging research themes. Additionally, we present a comprehensive analysis of current research areas, such as the correlation between autophagy and oxidative stress in the early stages of DR development, as well as the potential of NLRP3 inflammatory vesicles in various DR phenotypes, beyond the commonly studied inflammation and neoangiogenesis.